Answer :

e2xe - 3ydx + e2ye - 3xdy = 0

Rearringing the terms we get:

e2x + 3xdx = - e2y + 3ydy

e5xdx = - e5ydy

Integrating both the sides we get:

e5x + e5y = 5c’ = c

Ans: e5x + e5y = c

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses

Solve the differeMathematics - Board Papers

The general solutMathematics - Exemplar

The differential Mathematics - Exemplar

Form the differenMathematics - Board Papers

Solve the differeMathematics - Exemplar

Given that Mathematics - Exemplar

Find the equationMathematics - Exemplar